ASSESSMENT OF VITAMIN D STATUS AND CALCIUM-PHOSPHORUS METABOLISM IN POSTMENOPAUSAL WOMEN WITH OSTEOPOROSIS - Tatyana Simeonova (Peytchinski Publishing, 2020)
This study aims to assess vitamin D levels in women with postmenopausal osteoporosis and healthy women in menopause. Two groups of women over 50 years of age took part in the study - 41 women with osteoporosis and 22 without osteoporosis. The levels of vitamin D, parathormone, alkaline phosphatase, calcium and phosphorus were examined. 16 women with osteoporosis (39%) were with normal levels of vitamin D, 14 (34,1%) were with insufficiency, and 11 (26,9%) with deficiency of vitamin D. Within the control group, 8 women (36,4%) were with normal levels of vitamin D, 12 (54,5%) were with vitamin D insufficiency and 2 (9,1%) with deficiency. The patients with vitamin D deficiency were significantly older both in the osteoporosis group and the control group (r = -0.32, p<0.05). A negative correlation with the increase of parathormone levels among the patients with osteoporosis and vit D deficiency was found (r = -0.46, p<0.01). There is a significant statistical difference in the average values of BMI in both groups. The average value of BMI in the patients with osteoporosis is 24.2 while in the patients of the control group, it's 29.5 (p<0.0001). The same trend is seen in the patients with vitamin D deficiency both in the women with and the women without osteoporosis (24.4 to 28.2, respectively, p<0.05). The results show an overall bad status of vitamin D. 61% of the patients with osteoporosis and 63,6 % of the healthy controls have levels of vitamin D, showing either insufficiency or deficiency.